Intraspecific competition in Leucadendron xanthoconus (O.Knutze) K. Shun - Beukman, Ruth Pam (Department of Biological Sciences, 2017)
Sexual dimorphism, characteristic of a number of dioecious genera has inspired workers to generate hypotheses as regards intersexual and intrasexual competition. The Proteaceae genus Leucadendron is an example. In the Highlands State forest near Grabouw (Cape Province, South Africa) a number of Leucadendron xanthoconus populations exist. Here, an investigation for the detection of competition between and within the sexes was carried out, following the methods of Pielou (1960). The importance and the intensity of competition was estimated adopting the criteria pointed out by Welden and Slauson (1986). Based on the hypothesis that maternal investment is far greater than paternal investment at reproduction, female resource requirements were presumed to be larger than males. Consequently, females are the stronger competitors. Evidence for intersexual and intrasexual competition was found, the intensity of each type varied however with stand age. Intense negative interference by females on males was evidenced, supporting the idea that females were the stronger competitors. It was apparent that this caused male reproductive fitness to decline. Except for the 15-year-old plants there was no evidence to suggest niche partitioning between the sexes. Though competition was detected, its importance in relation to other factors in the community appeared to be low. Further studies are required to determine the processes operative in such dioecious populations. Depending on the degree of sexual dimorphism, does the importance and intensity of intraspecific competition vary? Does the pollination biology of dioecious, sexually dimorphic species influence niche partitioning?